Significance of Oct‐4 transcription factor as a pivotal therapeutic target for CD44+/24− mammary tumor initiating cells: Aiming at the root of the recurrence. (27th December 2022) - Sen, Utsav; Shanavas, Shanooja; Nagendra, Apoorva H.; Nihad, Muhammad; Chaudhury, Debajit; Rachamalla, Hari K.; Banerjee, Rajkumar; Shenoy P, Sudheer; Bose, Bipasha
Abstract: Breast cancer (BC) remains one of the deadliest and frequently diagnosed metastatic cancers worldwide. Cancer stem cells (CSCs) are the cell population within the tumor niche, having an epithelial to mesenchymal (EMT) transition phenotype, high self‐renewal, vigorous metastatic capacity, drug resistance, and tumor relapse. Identification of targets for induction of apoptosis is essential to provide novel therapeutic approaches in BC. Our earlier studies showed that Vitamin C induces apoptotic cell death by losing redox balance in TNBC CSCs. In this study, we have attempted to identify previously unrecognized CSC survival factors that can be used as druggable targets for bCSCs apoptosis regulators isolated from the TNBC line, MDA MB 468. After a thorough literature review, Oct‐4 was identified as the most promising marker for its unique abundance in cancer and absence in normal cells and the contribution of Oct‐4 to the sustenance of cancer cells. We then validated a very high expression of Oct‐4 in the MDA MB 468 bCSCs population using flow‐cytometry. The loss of Oct‐4 was carried out using small interfering RNA (siRNA)‐mediated knockdown in the bCSCs, followed by assessing for cellular apoptosis. Our results indicated that Oct‐4 knockdown induced cell death, changes in cellular morphology, inhibited mammosphere formation, and positive for Annexin‐V expression, thereby indicating the role of Oct‐4 in bCSC survival. Moreover, our findings also suggest the direct interaction between Oct‐4 and Vitamin C using in silico docking. This data, hence, contributes towards novel information about Oct‐4 highlighting this molecule as a novel survival factor in bCSCs.